C6 to C17 Organic Products from Artificial Photosynthesis Catalyzed by 2-Phenyl Indole (PI) Titanium Tetrachloride Complex (PI)2TiCl4: The Synergism of Hydroxyl Radicals - Arzoumanidis, Gregory G.; Paraskevas, Michail (Fine Chemical Engineering, 2025)
The newly discovered artificial photosynthesis process catalyzed by 2-phenyl indole (PI) and TiCl4 complexes, activated by visible light, produces long-chain oxygenated hydrocarbons up to C17. This process begins with the formation of α-carboxylic acid-ω-aldehyde compounds (C6 to C9), arising from a cascade of autocatalytic organotitanium complexes derived from (PI)2TiCl4. These complexes are formed via hydrolysis through ambient air humidity and the direct atmospheric capture (DAC) of CO2. Carbon chain growth utilizes system-generated formaldehyde as a feedstock. The initial C6 to C9 compounds can further couple into C12 to C17 derivatives through a radical mechanism initiated by hydroxyl radicals. A proposed mechanism explores the synergistic interaction between organotitanium catalysis and hydroxyl radicals. This development represents the only known heterogeneous catalytic system that autonomously captures CO2 and humidity from the atmosphere to subsequently produce long-chain oxygenated hydrocarbons using solar energy.